Young Cam Jansen and the dinosaur game - Adler, David A. (Adler, David A. Young Cam Jansen., 1996)
When fifth-grader Cam Jansen and her friend Eric go to a birthday party, she uses her photographic memory to solve the puzzle of the dinosaur count.